Information and its Presentation: Treatment Effects in Low-Information vs. High-Information Experiments. (3rd August 2018) - Andersen, David J.; Ditonto, Tessa
Abstract : This article examines how the presentation of information during a laboratory experiment can alter a study's findings. We compare four possible ways to present information about hypothetical candidates in a laboratory experiment. First, we manipulate whether subjects experience a low-information or a high-information campaign. Second, we manipulate whether the information is presented statically or dynamically. We find that the design of a study can produce very different conclusions. Using candidate's gender as our manipulation, we find significant effects on a variety of candidate evaluation measures in low-information conditions, but almost no significant effects in high-information conditions. We also find that subjects in high-information settings tend to seek out more information in dynamic environments than static, though their ultimate candidate evaluations do not differ. Implications and recommendations for future avenues of study are discussed.